Предмет: Математика, автор: davidova1995

Ребятки,помогите решить ;)

Приложения:

Ответы

Автор ответа: Yena
0

frac{log_2(1+frac{1}{x-1})}{log_2(x-1)*log_2x}+frac{log_2(1+frac{1}{x})}{log_2(x+1)*log_2x}=

=frac{log_2frac{x-1+1}{x-1}}{log_2(x-1)*log_2x}+frac{log_2frac{x+1}{x}}{log_2(x+1)*log_2x}=frac{log_2frac{x}{x-1}}{log_2(x-1)*log_2x}+frac{log_2frac{x+1}{x}}{log_2(x+1)*log_2x}

=frac{log_2x-log_2(x-1)}{log_2(x-1)*log_2x}+frac{log_2(x+1)-log_2x}{log_2(x+1)*log_2x}=

frac{log_2(x+1)*log_2x-log_2(x+1)*log_2(x-1)+log_2(x-1)*log_2(x+1)-log_2(x-1)*log_2x}{log_2(x+1)*log_2(x-1)*log_2x}=

=frac{log_2x(log_2(x+1)-log_2(x-1))}{log_2(x+1)*log_2(x-1)*log_2x}=frac{log_2(x+1)-log_2(x-1)}{log_2(x+1)*log_2(x-1)}=

frac{log_2frac{x+1}{x-1}}{log_2(x+1)*log_2(x-1)}

 

 

................................................................................................

Похожие вопросы
Предмет: Алгебра, автор: cергей16